Explorando Conceitos e Mecanismos de Memória Compartilhada Distribuída em Entrada/Saída Paralela - Osthoff, Carla; Bianchini, Ricardo; Seidel, Cristiana; Mattoso, Marta; Amorim, Claudio L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
Parallel applications from several areas, such as scientific computing and commercial databases, require high-performance input/output (I/O) systems. This paper proposes the exploitation of software-based distributed shared-memory (software DSM) concepts and mechanisms to optimize disk caching and, as a result, substantially improve the I/O performance of parallel systems. More specifically, the main contribution of the paper is a set of mechanisms that allow us: (a) to move the coherence of disk data to the main memory level; (b) to utilize a relaxed consistency model for the disk data accesses; and (c) to save disk cache space. In order to evaluate our ideas, we are currently implementing the DSMIO system for a prototype parallel database manager using the IBM-SP multicomputer system. Our preliminary results show that the database benchmarks that benefit the most from oursystem can achieve 99% reductions in execution time. We conclude that the exploitation of software DSM concepts and mechanisms indeed significantly improve the I/O performance of parallel database applications.